2017 IEEE Conference on Computer Vision and Pattern Recognition (CVPR) 2017
DOI: 10.1109/cvpr.2017.105
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Diffusion on Region Manifolds: Recovering Small Objects with Compact CNN Representations

Abstract: Query expansion is a popular method to improve the quality of image retrieval with both conventional and CNN representations. It has been so far limited to global image similarity. This work focuses on diffusion, a mechanism that captures the image manifold in the feature space. The diffusion is carried out on descriptors of overlapping image regions rather than on a global image descriptor like in previous approaches. An efficient off-line stage allows optional reduction in the number of stored regions. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
241
1
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 159 publications
(247 citation statements)
references
References 54 publications
4
241
1
1
Order By: Relevance
“…Other effective methods include burstiness handling [77] (discussed in Section 3.4.3), considering the different inlier ratios between the query and target objects [121], etc. In the second type of methods, effective region proposals [122] or multi-scale image patches [123] can be used as object region candidates. In [123], a recent state-of-the-art method, a regional diffusion mechanism based on neighborhood graphs is proposed to further improve the recall of small objects.…”
Section: Small Object Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…Other effective methods include burstiness handling [77] (discussed in Section 3.4.3), considering the different inlier ratios between the query and target objects [121], etc. In the second type of methods, effective region proposals [122] or multi-scale image patches [123] can be used as object region candidates. In [123], a recent state-of-the-art method, a regional diffusion mechanism based on neighborhood graphs is proposed to further improve the recall of small objects.…”
Section: Small Object Retrievalmentioning
confidence: 99%
“…In the second type of methods, effective region proposals [122] or multi-scale image patches [123] can be used as object region candidates. In [123], a recent state-of-the-art method, a regional diffusion mechanism based on neighborhood graphs is proposed to further improve the recall of small objects.…”
Section: Small Object Retrievalmentioning
confidence: 99%
“…We observed that the step ∆ [27]. MAC: max-pooling [40]; GeM: generalized-mean pooling [29]; D: diffusion [12]. All results with supervised whitening [21].…”
Section: Methodsmentioning
confidence: 98%
“…Recently, Iscen et al [21] and Yang et al [39] outperformed the state of the art on several public image retrieval datasets through the application of the diffusion process to R-MAC descriptors [15]. The reason for the success of diffusion for retrieval [40] is that it permits to find more neighbors that are close to the query using the manifold representation, than using the Euclidean one.…”
Section: Introductionmentioning
confidence: 99%